Lateralized cerebellar connectivity differentiates auditory pathways in echolocating and non-echolocating whales - Sophie Flem; Gregory Berns; Ben Inglis; Dillon Niederhut; Eric Montie; Terrence Deacon; Karla L. Miller; Peter Tyack; Peter F. Cook (PLoS ONE, 2025)
We report the first application of diffusion tractography to a mysticete, which was analyzed alongside three odontocete brains, allowing the first direct comparison of strength and laterality of auditory pathways in echolocating and non-echolocating whales. Brains were imaged post-mortem at high resolution with a specialized steady state free precession diffusion sequence optimized for dead tissue. We conducted probabilistic tractography to compare the qualitative features, tract strength, and lateralization of potential ascending and descending auditory paths in the mysticete versus odontocetes. Tracts were seeded in the inferior colliculi (IC), a nexus for ascending auditory information, and the cerebellum, a center for sensorimotor integration. Direct IC to temporal lobe pathways were found in all animals, replicating previous cetacean tractography and suggesting conservation of the primary auditory projection path in the cetacean clade. Additionally, odontocete IC-cerebellum pathways exhibited higher overall tract strength than in the mysticete, suggesting they may play a role in supporting the rapid sensorimotor integration demands of echolocation. Further, in the mysticete, contralateral right IC to left cerebellum pathways were 17x stronger than those between left IC and right cerebellum, while in odontocetes, the laterality was reversed, and left IC to right cerebellum pathways were 2-4x stronger than those between right IC and left cerebellum. This lateralization may also relate to echolocation. Right cerebellum is responsible for integrating sensory and motor signals from the left cortical hemisphere, and in odontocetes, this hemisphere likely controls the contralateral right-side phonic lips, which have been empirically implicated in the production of echolocation clicks. We also found differences in the specific subregions of cerebellum targeted by the IC between the mysticete and odontocetes, some of which may also bear on hearing and vocal production. This study establishes foundational knowledge on mysticete brain connectivity and extends knowledge on pathways supporting hearing and auditory-motor integration across the order Cetacea.